Christian Stewardship: Reinterpreting Psalm 24:1 in the Context of Environmental Awareness Education - Agustina Pasang (Jurnal Teologi Injili, 2026)
This article aims to find the concept of service in Psalm 24: 1 as a theological basis for the context of environmental awareness education using research methods with the content analysis approach and literature study. The results showed that the earth and all of its contents belonged to God that contain strong ethical and pedagogical implications for believers in maintaining ecology. In this case the service is understood as a moral obligation but also as a form of participation of believers in carrying out God's mission towards the world. Christian stewardship affirms Divine ownership of creation, Stewardship as a Christian Ecological Ethic, stewardship encompasses social, spiritual, and ecological responsibilities. This article also proposes the integration of ecotheological values in the Christian education curriculum as one of the strategies to foster concern for the environment based on faith education, thus Christian education can become a transformative agent in building a culture of sustainable environmental awareness.